Dynamic impact of China's stock market on the international commodity market. (June 2019) - Wen, Shaobo; An, Haizhong; Huang, Shupei; Liu, Xueyong
Abstract: It is generally believed that the international commodity markets' downturn is attributed to China's stock markets collapse. To verify this, this paper assesses the influence of Shanghai (securities) stock exchange composite (SSEC) index on S&P GSCI total returns, a leading commodity composite index from August 31, 2006, to September 19, 2016. We implement wavelet transform to extract the approximations of SSEC and GSCI. Furthermore, we use the state space model to determine the margin between SSEC and GSCI as well as display the margin dynamic evolution over time. The margin denotes the units of GSCI change when SSEC increases a unit, which can display China's stock (equity) influence (CEI) on the international commodity market. We found that CEI reached its peak in 2007, then experienced two steep declines and an immediate mild rebound, and eventually hovered at a historically low level. Moreover, each inflection point of CEI could correspond to a specific international economic event, which indicates that the change of CEI is influenced by exogenous variables, especially the absolute increment of GDP and the U.S. dollar index. The influence of China's stock market on the international commodity market is not as great as believed and the diversification benefit still exists for the construction of portfolio. In addition, the change of China's stock market influence is closely related to exogenous factors, which deserves more attention for policy making to avoid unnecessary trade and monetary friction owing to misjudgment. Highlights: We examine the evolution of China's stock market influence (CEI) on the international commodity market. The analysis is based on both wavelet transform and the state space model. From 2006 to 2016, CEI has not showed a growth trend and eventually hovers at a historically low level. The evolution of China's stock market influence (CEI) is driven by the absolute increment of the countries' gross domestic product (GDP) and U.S. Dollar index (USDX) at the same time.